Heat-related illnesses: a scoping review of health system strategies, emergency responses and interventions in heat-prone areas - Peace U. Bassey; Faith A. Ngwu; Obinna C. Shimobi; Amarachukwu B. Isiaka; Chigbo C. God’swill; Christine Hosein; Benson C. Ephraim-Emmanuel (BMC Public Health)
Abstract Background and aim In order for effective heat emergency responses to be achievable, it is essential that healthcare delivery systems are made as heat-resilient as possible, alongside adoption of region-specific public health interventions. This review was thus aimed at identifying health system strategies, emergency responses and public health interventions adopted to ameliorate the harmful health effects of heat-related illnesses in heat-prone areas of the world. Methods We performed a scoping review whose documentation was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Literature included were original articles published in English, policy review documents and program evaluations, population-based intervention studies, and other relevant gray literature. An electronic search of the PubMed, Web of Science, and World Health Organization (WHO) Global Health Observatory databases was performed in October 2024, using search terms developed from the search keywords. Results Thirteen studies were included in this review, out of which 6 were policy-based documents on heat action plans while 7 were observational studies describing the application and effectiveness of heat action plans as well as susceptible members of populations to heat-related illnesses (HRIs). Nine of them were conducted in High-Income-Countries (HICs), while 4 were conducted in Low- and Middle-Income-Countries (LMICs). Eight of these articles (61.5%) were categorized as having good quality, while others were of fair quality. The different studies were identified to report various health system implementation strategies of heat action plans (HAPs), the targeted populations of these HAPs, emergency response actions, as well as public health interventions that contributed in reducing the impact of HRIs. Conclusions Heat action plans are necessary to be tailored to the needs and resources of every heat-prone area, for effective development of heat-resilient health systems. Further research on quantifiable estimates of effects of HRIs prevention strategies are necessary to enhance their applicability during heat emergencies.